2008
DOI: 10.1002/pip.818
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Boron‐doped region using spin‐on dopant: investigation on the impact of metallic impurities

Abstract: Investigation on the electrical properties of p+‐doped regions formed by spin‐on‐dopant (SOD) technique was achieved. Using this technique, boron‐diffused regions were formed on both p‐type and n‐type float zone wafers. Homogeneous sheet resistances were obtained for both types of wafers. Bulk properties were investigated by measuring effective carrier lifetime. An iron contamination was observed after the boron diffusion step and interstitial iron concentrations were deduced from lifetime measurements. More i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…2, the spin-on dopant (SOD) boron diffusion induces a strong drop in the effective lifetime for all samples. A previous work, based on the study of the influence of the boron SOD technique on the electrical properties of single-crystalline wafers, showed that this effect was mainly related to the introduction of iron initially present in the deposited film [10]. This impact of this homogenous contamination on mc-Si wafers is presented in Fig.…”
Section: Effects Of the Boron Diffusionmentioning
confidence: 95%
“…2, the spin-on dopant (SOD) boron diffusion induces a strong drop in the effective lifetime for all samples. A previous work, based on the study of the influence of the boron SOD technique on the electrical properties of single-crystalline wafers, showed that this effect was mainly related to the introduction of iron initially present in the deposited film [10]. This impact of this homogenous contamination on mc-Si wafers is presented in Fig.…”
Section: Effects Of the Boron Diffusionmentioning
confidence: 95%
“…A estrutura da célula solar foi reotimizada e o processo foi projetado para reduzir a resistência série e as perdas por recombinação nos dispositivos [7]. Esta empresa também está desenvolvendo células solares bifaciais [8] em substratos tipo n. Um resultado importante foi obtido por MIHAILETCHI et al [3] em células solares de 140 cm 2 de área processadas em lâminas finas de Si-FZ tipo n, com difusão de boro para formar o emissor frontal.…”
Section: Introductionunclassified
“…A obtenção desta região dopada com alta qualidade e baixo custo ainda é um problema em discussão e a aplicação de dopantes por spin-on tem sido estudada para solucioná-lo [7,13,14,15].…”
Section: Introductionunclassified
“…The spin-on dopant technique offers single-sided diffusion, but it can suffer from contamination by metallic impurities initially present in the spin-on dopant film [11]. The ink-jet printing technique, on the other hand, has the added advantage of creating selective emitters.…”
mentioning
confidence: 99%
“…glass formed by gaseous BBr 3 [5]- [9] and BCl 3 [10] precursors, diffusion from spin-on boron source [11], inkjet-printed boron source [12], [13], and atmospheric pressure chemicalvapor-deposited boron silicate glass (BSG) [14], as well as conventional boron ion implantation [15], [16] and plasma ion implantation [17] followed by thermal diffusion. The various doping methods have their unique advantages and disadvantages.…”
mentioning
confidence: 99%